CLINICAL-IMMUNOLOGY EFFICIENCY OF CONSERVATIVE TREATMENT OF PATIENTS WITH CHRONIC TONSILLITIS ASSOCIATED WITH EPSTEIN - BARR VIRUS INFECTION - A. S. Krasnitskaja; A. S. Shitihina (Acta Biomedica Scientifica)
To assess clinical-immunological efficiency of an immunomodulator reaferon-ES-lipinta 70 people with chronic tonsillitis (41 women and 29 men) were surveyed in dynamics. Among them. 30 people had Epstein — Barr virus infection (1st group), and in 40 people (the 2nd group) Streptococcus pyogenes was diagnosed. The features of local immunity at chronic tonsillitis associated with the EBV infection were revealed. They are characterized by increase of IL-10 in the high point of an illness and of IL-1β, IL-6 and IL-4 on the 7th day of research in saliva of patients with the EBV infection. Conservative treatment of patients with chronic tonsillitis associated with the EBV infection of the reaferon-EC-lipint provided acceleration of normalization of a local profile of cytokine and was clinically effective in 63,3 % of cases.